Peningkatan Hasil Belajar Siswa dan Sikap Bernalar Kritis Dalam Pak Dengan Model PBL Fase A Kelas Dua - Soniveriyus Lahagu; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The ability to think critically is one of the hopes for every teacher towards their students. The ability to think critically of students at SD Negeri 075021 Ombolata Salo'o is still relatively low, so that linearly student learning outcomes are low, therefore the existing problems will be tried to be overcome with a model. more interesting learning is PBL. This research aims to find out whether the application of the problem based learning model can improve student learning outcomes in the Catholic Religion Learning process and whether the use of this model can also improve students' critical reasoning in Catholic religious learning. The method used is classroom action research with the variable being PBL learning to improve students' learning outcomes and critical thinking abilities. The findings in this research were that in the first cycle an average score of 74.76 or 66.66% was produced, there were still 2 students who had not progressed. In the second cycle the average score was 91.66 or 100% completion of learning outcomes for all students. The value of the critical reasoning attitude increased from 70 to 89.16 The implication of this research is that the PBL method can be used by teachers creatively, the teacher's creativity in using the student center learning method leads to increased completeness of learning outcomes and an increase in students' critical reasoning attitudes.